Four new species of the genus Miridiba Reitter (Coleoptera: Scarabaeidae: Melolonthinae) from China - Gao, Chuan-Bu; Bai, Ming; Fang, Hong; Yu, Zhi-Guo (Zootaxa, 2018)
Four new species of the genus Miridiba Reitter, 1902 from South China are described and illustrated: Miridiba (Miridiba) bannaensis Gao & Fang, new species, M. (M.) kuatunensis Gao & Fang, new species, M. (M.) xingkei Gao & Fang new species and M. (M.) youweii Gao & Fang, new species. Miridiba (M.) tuberculipennis obscura Itoh, 1995 is raised to species level. Miridiba (M.) obscura Itoh, 1995 and M. (M.) tuberculipennis (Moser, 1913) are newly recorded for China. A catalogue of Miridiba species from China is provided. [Zoobank registrations: Miridiba bannaensis Gao & Fang, new species: LSID: urn:lsid:zoobank.org:act:0AEA5EFC-0914-437A-AEF6-C2685247E427 Miridiba kuatunensis Gao & Fang, new species: LSID: urn:lsid:zoobank.org:act:148F9BA8-5666-40DC-A209-25C4B68D5CD5 Miridiba xingkei Gao & Fang, new species: LSID: urn:lsid:zoobank.org:act:65A3141D-C7AC-4E89-BB20-5F5CFFA4D58E Miridiba youweii Gao & Fang, new species: LSID: urn:lsid:zoobank.org:act:DDA98D6C-5753-4F82-A49A-D9C7913DCFC2]